Dopant concentration induced tuning of emission in Eu3+-doped zirconia nanoparticles. (April 2022) - King, Abhishek; Singh, Rahul; Anand, Rahul; Behera, Shantanu K.; Nayak, Bibhuti B.
Abstract: Eu 3+ -doped zirconia has been considered an efficient phosphor material due to its multi-colour emissive photoluminescence properties. Tuning of emission colour is possible by changing the Eu 3+ -ions concentration and excitation wavelength. The influence of Eu 3+ -ions and excitation wavelength on the emission intensity, asymmetric ratio, CIE coordinates, and Judd-Ofelt parameters of the Eu 3+ -doped zirconia nanophosphors have been explored in this work. Ultra-fine nano-sized particles of pure tetragonal zirconia were observed when the samples were calcined under an argon atmosphere at 800 °C. The expansion and distortion of tetragonal zirconia has been confirmed from XRD and Raman Spectra of Eu 3+ -doped zirconia samples, respectively. The XPS analysis suggested elemental composition and incorporation of trivalent state of Eu-ions in Eu 3+ -doped zirconia sample calcined under argon calcination condition. Further, emission spectra of Eu 3+ -doped zirconia samples have been investigated at the excitation wavelength of 240 nm, 393 nm, and 463 nm. The emission spectra of 3 mol % and 6 mol % Eu 3+ -doped zirconia samples revealed several emission peaks in the range of 580–710 nm corresponding to the Eu 3+ -ions transition of 5 D0 → 7 Fj (=0 to 4) . However, due to lower emission intensity, these transitions were not clearly visible up to 1 mol % Eu 3+ -ions. The CIE coordinates confirmed the tuning of emission colour in Eu 3+ -doped zirconia nanophosphor at different excitation wavelengths. The Judd-Ofelt parameters also suggested that the Eu 3+ -doped zirconia may be utilized for better optical gain. So, nano-sized Eu 3+ -doped zirconia phosphor materials may consider as a potential candidate for different luminescence applications. Graphical abstract: Image 1 Highlights: Eu 3+ -doped t-ZrO2 nanoparticles have been prepared under Ar calcination atmosphere. XRD and Raman suggest lattice expansion and distortion of t-ZrO2, respectively. Emission of 3 and 6 mol% Eu 3+ -doped ZrO2 varied with excitation wavelengths. Asymmetric ratio and CIE coordinates suggest tuning of emission via different λex .